2001
DOI: 10.1176/appi.ajp.158.12.2015
|View full text |Cite
|
Sign up to set email alerts
|

Low Level of Brain Dopamine D2 Receptors in Methamphetamine Abusers: Association With Metabolism in the Orbitofrontal Cortex

Abstract: Lower levels of dopamine D2 receptor availability have been previously reported in cocaine abusers, alcoholics, and heroine abusers. This study extends this finding to methamphetamine abusers. The association between level of dopamine D2 receptors and metabolism in the orbitofrontal cortex in methamphetamine abusers, which replicates previous findings in cocaine abusers, suggests that D2 receptor-mediated dysregulation of the orbitofrontal cortex could underlie a common mechanism for loss of control and compul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
246
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 834 publications
(276 citation statements)
references
References 50 publications
27
246
3
Order By: Relevance
“…Similar to observations in obese individuals, a significant association between D2 receptor availability and metabolism in prefrontal regions was observed in drug-addicted subjects (cocaine, methamphetamine, and alcohol) [31,32,33]. The same finding in individuals at high familial risk for alcoholism [34] suggests that these abnormalities precede the change in behavior.…”
Section: Do Pet Studies Support the Concept That Obesity Is Caused Bysupporting
confidence: 68%
“…Similar to observations in obese individuals, a significant association between D2 receptor availability and metabolism in prefrontal regions was observed in drug-addicted subjects (cocaine, methamphetamine, and alcohol) [31,32,33]. The same finding in individuals at high familial risk for alcoholism [34] suggests that these abnormalities precede the change in behavior.…”
Section: Do Pet Studies Support the Concept That Obesity Is Caused Bysupporting
confidence: 68%
“…For example, drugs of abuse cause a reduction in the availability of D 2 -like receptors (22)(23)(24)(25)(26), and D 2 -like receptors also appear to be down-regulated relative to D 1 -like receptors in other neuropsychiatric disorders, including schizophrenia (27,28). Previous work in our laboratory has shown that D 2 down-regulation in response to drugs of abuse is mediated by interaction with GASP-1 (5).…”
Section: Discussionmentioning
confidence: 91%
“…We have shown that the reductions in striatal D 2 receptors in the detoxified drug-addicted subjects were associated with decreased metabolic activity in orbitofrontal cortex (OFC), anterior cingulate gyrus (CG) and dorsolateral prefrontal cortex (DLPFC; figure 1; Volkow et al 1993Volkow et al , 2001Volkow et al , 2007a. Since OFC, CG and DLPFC are involved with inhibitory control (Goldstein & Volkow 2002) and with emotional processing (Phan et al 2002), we had postulated that their improper regulation by DA in addicted subjects could underlie their loss of control over drug intake and their poor emotional selfregulation.…”
Section: Inhibitory Control/emotional Reactivity Circuit In Addictionmentioning
confidence: 99%